Fulvifomes paraensis sp. nov. (Hymenochaetaceae, Basidiomycota), a new species from the floodplain forests of the Brazilian Amazon - Mendes-Freire, Richard B.; Vilhena, Maria Do Perpétuo S. P.; Soares, Adriene M. Da Silva (Phytotaxa, 2025)
Fulvifomes is a monophyletic genus of Hymenochaetaceae (Basidiomycota), with a cosmopolitan distribution and ecological importance. Specimens of Fulvifomes were collected from floodplain forest islands in the Brazilian Amazon. Morphological and molecular phylogenetic analyses revealed a new species, Fulvifomes paraensis sp. nov., mainly characterized by its pileate basidioma, broadly attached to dimidiate, hyphal system monomitic in context to subdimitic in trama, and basidiospores broadly ellipsoid to subglobose. This species was found on dead trunks of Mora paraensis, a tree species that is endemic to floodplain areas of the eastern Amazon. Additionally, Fulvifomes kawakamii is reported for the first time in floodplain forests. Notes and illustrations for these two species, and an identification key for the species of Fulvifomes with molecular data from Brazil are provided.